Design of Portable Quadrupole Mass Spectrometry Control System Based on FPGA - GE Wei-min; XU Chun-hua; LIN Li-quan; CHEN Jia-xin; WU Man-man; QIAO Jia (Zhipu Xuebao, 2023)
To meet the requirements of miniaturization and low power consumption of portable instruments, a set of lower computer control system of portable quadrupole mass spectrometry was designed. The new control system was developed based on Xilinx spartan-6 series field programmable gate array (FPGA) platform. A single FPGA chip was used to replace the cumbersome architecture of traditional multiple chip combinations. The original W5500\MCU\DSP\DDR and other functional chips on the main control circuit board were removed, and the scanning, control, acquisition, storage, data processing, high-speed transmission and other functions realized by these chips were integrated into the same FPGA chip. The control system mainly communicated with the lower computer through the upper computer. The lower computer controlled the DAC voltage to scan the quadrupole, and at the same time linked the 16 bit ADC to collect data. The collected data was processed by some columns of algorithms, and then a large amount of data was accumulated and compressed, stored in the chip. Finally, the whole spectrum data was integrated according to the frame format and uploaded to the upper computer for displaying. The lower computer control system also integrated tuning control, feedback control, high voltage control and other functional modules. The difficulty in the design of the whole system lied in the high utilization of chip resources, which required a reasonable allocation of various chip resources and a balance in performance, speed and area. Compared with the existing miniaturized quadrupole mass spectrometry control system, the new control system not only saved the chip cost on the premise of unchanged function and performance, but also saved about 2.7 W in the power consumption of the master hardware board, which was about 37% of the power consumption of the original board, and reduced about 20 cm2 in the area of the master hardware board, which was about 10% of the area of the original board. The performance of the portable quadrupole mass spectrometer lower computer control system was fully verified by the 25 volatile organic compounds (VOCs) mixed standard test experiment, and was successfully applied in the portable quadrupole mass spectrometer. This design has high technology portability and practical value for similar miniaturized instruments. At this stage of the design, it is not possible to integrate all the functions of the instrument and realize a real single-chip lower computer control system, and the integrated functional modules need to be further optimized. Under the demand of miniaturization and low power consumption of portable instruments, the concept and design of integration will go further and further, and will slowly and truly achieve simple substitution for cumbersome, single substitution for combination, so as to make the concept of portability to the extreme and obtain the maximum value with the least consumption.